Assessment of Inhaler Misuse in Asthmatic Patients. - Mahdi, Suha A.; Mohammed, Amar K.; Alani, Wasan J. (Journal of the Faculty of Medicine Baghdad, 2014)
J Fac Med Baghdad 2014; Vol.56, No .2 Received Dec .2013 Accepted Mar. 2014 Back ground: Metered dose inhalers (MDIs) are important devices used in treatment of asthma. It has got lots of benefits and some drawbacks depending on usage technique, with proper technique and training the drawbacks can be minimized. Objectives: Estimate the percentage of asthmatic patients using the metered dose inhalers improperly both in technique and dose, and detect the main factors associated with its improper use. Patients and methods: Cross sectional study done from beginning of Jan.-end of May 2013, convenient sampling (150 asthmatic patients)were participated, the questionnaires were filled by direct interview with patients and asking them the steps of inhaler use after take the verbal consent, P-value <0.05 considered statistically significant. Results: From 150 asthmatic patients (34%) of participant can use the inhaler correctly while others were misusing it, all of elderly above 57year, (74.53%) of female gender,(93.33%) of participants who live in rural area, (89.16%)of not employed, and (90%) of low educational level were misusing the inhaler, there was statistically significant association between the use of inhaler and participants who use other drugs to treat asthma rather than inhaler, and those who use steroid inhalers more than two puffs per each time, there was statistically significant association between the use of inhaler and by whom the participants were learned, we found that (65.22%) of participants who learned by specialist were correctly use the inhaler while(34.78%)were misusing it, and (85.71%) of patients who learned by general practional and all of those learned by pharmacist and others like relatives were misuse the inhaler. Conclusion: Two third of asthmatic patients were misusing the inhaler. and the main factors that’s associated with misusing of inhaler were; old age, female gender, not employed, low educational level, use of other drugs to treat asthma rather than inhaler, use steroid inhaler more than two puff in each time of use, and who learned by general doctors and pharmacist or others (relatives).